Model Mental Konseptual Siswa Sekolah Menengah Pertama dalam Memahami Konsep Faktor Prima - Sukiyanto Sukiyanto; Syamsulrizal Syamsulrizal; Dewi Anggreini (Jurnal Tadris Matematika, 2021)
This study aimed to identify students' conceptual mental models in understanding the concept of prime factors. This study uses a qualitative and descriptive approach, using subjective analysis. Subjects in this study amounted to 71 students in class VII. The research instrument used is a test consisting of two questions. At the same time, the data collection techniques use interviews. Based on the results of data analysis, it was found that as many as subjects were included in the conceptual mental model. Furthermore, from the research results, it can be seen that students' conceptual mental models in understanding prime factors of a number, namely, students can use factor trees and understand prime numbers. This is supported by the results of interviews with three subjects stating that students can prove that 5 and 3 are prime factors of N while 15 and 45 are not prime factors of N; this is because 3 and 5 are prime numbers while 15 and 45 are not numbers. Primes In addition, students can prove that is the prime factorization of M.